The Virgin Mary in the Middle Ages and the Renaissance: Devotion and Iconography - Salvador-González, José María (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to investigate some of the numerous ways in which Christianity venerated and represented the Virgin Mary in the Middle Ages and the Renaissance. Fifteen researchers in various areas of the Arts and Humanities have brought together here their efforts to address in part this inexhaustible objective. The reprint is divided into two main parts. In one of them, composed of six chapters, we study some of the several ways in which the Christian faithful rendered worship and devotion to the Virgin Mary during the more than one thousand years under consideration. The other part, made up of seven chapters, analyzes various iconographic manifestations through which medieval and Renaissance Christians made their devotion to the mother of Christ visible in pictorial or sculptural forms. Therefore, this reprint will be very useful not only for specialists in Christian studies, especially in Marian themes but also for those interested in the development of the societies and cultures of medieval and Renaissance Europe.